In vitro induction and culture of adventitious buds in epicotyl segments of sour orange - Silva, Rosely Pereira da; Mendes, Beatriz Madalena Januzzi; Filho, Francisco de Assis Alves Mourão (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the induction and formation of adventitious buds in sour orange explants through the use of plant regulators. In vitro organogenesis experiments were conducted to evaluate the effect of BAP, TDZ, and KIN in different concentrations and under two light conditions; BAP and KIN, combined or not with NAA; BAP and KIN, separately or in combined concentrations. Sour orange epicotyl segments (1 cm length), from in vitro germinated plants, were used as explants. In order to induce bud formation, the explants were cultured in MT medium with or without the addition of plant regulators. The material was cultivated at 27ºC in the absence of light for 30 days, followed of culture under a 16-hour photoperiod. The experimental design was completely randomized, with four or five replicates, depending on the experiment; each replicate comprised one Petri dish with 20 explants. After 60 or 70 days of cultivation, the percentage of responsive explants and the number of buds were evaluated. The addition of BAP to the culture medium, combined or not with ANA, and in combinations with CIN, induces better organogenic response.